The time machine - Wells H. G. 1866-1946; H. G. Wells (Great Britain : William Collins, 2017)
H. G. Wells' The Time Machine, from 1895, popularized the idea of a vehicle that allows its user to travel intentionally and selectively across time, and indeed Wells is credited with coining the very term "time machine." The Time Traveler of this novella tests his time machine with a leap forward to the year 802,701 A.D., to find that evolution has produced two very different post-human races - the peaceful and childlike fruit-eating Eloi and the Morlocks - pale, darkness-dwelling troglodites who operate the underground machinery that makes this seeming paradise possible.
M
estimates